The architecture of proposed REDD schemes after Bali: facing critical choices - Karsenty, A. (2008)
Rules governing the REDD (Reductions of Emissions from Deforestation and Degradation) scheme have yet to be established. Different national interests compete within the debate on baselines in order to maximize expected gains. The scheme could have a deleterious impact on the carbon market through massive hot air creation (fake emission reductions), and ultimately on the current international climate change regime derived from the cap-and-trade architecture adopted by the Kyoto Protocol. The political economy of avoided deforestation is frequently overlooked as is the issue of additionality, although both of them are more critical with deforestation at national level than they could be with project-based CDM. An alternative REDD architecture which relies on a special fund would not only allow protection of the carbon market against massive fl ooding by non additional credits, but could also help fi nance potentially effi cient policies and measures.Sustaining long-term adequate funding is still an issue to be addressed on a multilateral basis.